Training of Natural Dyes Production and Its Application for Batik at Batik Manggar Gading SMEs - Diah Pratiwi (Yogyakarta State University, 2019)
The community empowerment activity have been conducted with the topic “Training of Natural Dyes Production and its Application for Batik” that involves researchers and members of Batik Manggar Gading SMEs. The purpose of this project is introducing natural dyes as batik dyes to batik craftmen in Batik Manggar Gading SMEs. Natural dyes has some advantages than synthetic dyes. In addition to typical colour, natural dyes was claimed to be more eco-friendly product so it has higher market value. The develompent of knowledge and skills in production process of batik natural dyes is expected to increase income and livehood of batik craftsmen. Community empowerment is made through two activities, namely field survey and training. Field survey was conducted to identify and collect relevant information about production process in Batik Manggar Gading SMEs. Meanwhile, the training was held at Batik Manggar Gading SMEs consists of two types of training. The first training, participants are given the knowledge about the potential of natural ingredients that can be used as natural dyes and practice how to extract/ create a substance the color of nature. The second, participant are given training about deployment process of batik coloring used natural dyes. As a result of these activities, 22 members of SMEs can make natural dyes batik. Natural dyes batik is a result of the utilization of biodiversity in pushing the economic income of the community. Natural dyes batik can be a Indonesia flagship product particular Gunungkidul Regency in international market.